Navigating the Intersection of Vulnerability and Resilience: The Lived Experiences of the Abused Foster Children in South Africa. - Decent Munzhelele; Mukhethwa Doreen Mugivhi; Phoke Alpha Rakgwata (CV. RADJA PUBLIKA, 2025)
Foster care is the temporary placement of a child who needs care and protection. The child is placed in the care of a suitable person who is not the parent or guardian of the child. This study aims to critically explore the nuanced experiences of foster children who have endured abuse, focusing on the intersections between vulnerability and resilience within the South African foster care system. The primary objective of this article is to understand how abuse shapes the psychological, emotional, and social well-being of these children, while also identifying the factors that contribute to their resilience and capacity to overcome adversities. Utilizing a qualitative research approach, the study adopts an exploratory research design, which allows for an in-depth examination of existing literature and secondary data sources relevant to the subject matter. As a comprehensive desktop study, the research synthesizes a range of qualitative data derived from reports, academic articles, governmental and non-governmental documents, and other pertinent resources. Thematic data analysis was employed to systematically identify and interpret recurring themes and patterns in the data, with a particular focus on the vulnerabilities these children face and the adaptive strategies they develop to navigate their challenges. The findings reveal a complex and multifaceted picture of foster children's lives, where the Psychological Trauma and Long-term effects of abuse are compounded including, stigma and Social Exclusion in their foster care system, role of Cultural and Societal Factors in Shaping Resilience and barriers to access support services have been found as the central findings. The findings of this article intend to inform and influence policymakers, the department of social development to provide the conducive environment that is more effective for child protection.